OPTIMIZATION OF THE CHEMICAL COMPOSITION AND CONCENTRATION OF SOIL SOLUTION OF SOILS OF DESERT ZONE FOR NUTRITION OF PLANTS - Sidikov Saidjon, Ermatova Munojat, Tashmetova Nigora (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The chemical composition and concentration of the soil solution of the soils of the desert zone under intensive farming were studied. As a result of studies, it was found that at a low concentration of soil solution the plant develops poorly, it cannot absorb a sufficient amount of nutrients and, conversely, a high concentration of the solution also negatively affects the plant. The optimal concentration is the most favorable environment for plant development, which helps to accelerate the absorption of nutrients by plants and ensure high crop yields. The composition and reaction of the soil solution in the practice of agriculture is regulated by the application of fertilizers, soil treatment, and land reclamation. For example, fertilizers are added to enrich the soil with nutrients, soil cleaning is carried out to eliminate salinization and others. The composition of the soil solution, the concentration and ratios of various compounds in it are subject to seasonal variation during the growing season. This is facilitated by the process of plant nutrition. Especially, in the middle of the growing season (July, August), noticeable changes occur in the composition of the soil solution. The results obtained are of great theoretical and practical importance in the knowledge of metabolic reactions in the soil-absorbing complex between the absorbed ions and ions in the solution; actions of fertilizers, irrigation and processing technologies on this process; scientifically sound application of fertilizers, as well as in the educational process of higher educational institutions.